Effect of temperature gradient on parametric X-Ray radiation. Status of experiment; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Mkrtchan A. R. Alpik Rafaelovich; Mkrtchyan A. Artak; Potylitsyn A. P. Alexander Petrovich; Kocharian V. R. Vagan Rashidovich; Nikoghosyan V. Valery; Vukolov A. V. Artem Vladimirovich; Novokshonov A. I. Artem Igorevich; Gogolev A. S. Aleksey Sergeevich; Wagner A. R. Aleksandr Rudolfovich; Movsisyan A. Artur (Parametric X-Radiation, 2015)
Title screen.